Design and Policy Framework for Climate-Optimized Electric Vehicle Battery Systems in Bangladesh: Engineering Solutions for Sustainable Mobility and Global Integration - Akhter, Afroza (European Journal of Applied Sciences, 2026)
The rapid global transition toward electric vehicles (EVs) represents a critical shift in the automobile industry, driven by the urgent need to reduce greenhouse gas emissions and achieve sustainable mobility. However, the adoption of EV technology in developing countries such as Bangladesh presents unique challenges, particularly due to climatic conditions, infrastructural limitations, and policy gaps. This thesis investigates the design and policy framework for climate-optimized electric vehicle battery systems in Bangladesh, with a focus on enhancing performance, safety, and long-term sustainability. A key challenge addressed in this study is the impact of Bangladesh’s tropical climate on lithium-ion battery performance. High ambient temperatures and humidity levels contribute to thermal stress, accelerated degradation, and reduced efficiency of battery systems. To address this issue, the research explores various battery thermal management systems (BTMS), including air cooling, liquid cooling, and phase-change materials, through simulation-based analysis. The objective is to identify the most effective and economically feasible solution suitable for local environmental conditions. In addition to engineering design, this study examines the current policy landscape governing electric mobility in Bangladesh. It identifies gaps in regulatory frameworks, infrastructure development, and technological adaptation that hinder the widespread adoption of EVs. By integrating engineering insights with policy analysis, the research proposes a comprehensive framework aimed at supporting the development of a resilient EV ecosystem. The findings of this study contribute to both academic and practical domains by offering a localized approach to EV technology adaptation while aligning with global sustainability goals. Ultimately, this research provides a foundation for future innovation, policy formulation, and international collaboration in advancing Bangladesh’s automobile sector toward a more sustainable and globally integrated future.